A simple and robust liquid chromatography tandem mass spectrometry assay for determination of plasma free metanephrines and its application to routine clinical testing for diagnosis of pheochromocytoma. (25th July 2019) - Shen, Ying; Luo, Xia; Li, Huijun; Guan, Qing; Cheng, Liming
Abstract: Plasma free metanephrines (PFMs) have high sensitivity for detecting pheochromocytoma (PCC). Herein, we developed a simple and reliable liquid chromatography tandem mass spectrometry assay for PFMs determination in Chinese population. PFMs were enriched by SPE without requiring extract evaporation or the use of buffers containing nonvolatile salts. The analytes were analyzed in multiple reaction monitoring mode. Inter‐ and intra‐assay precisions were ≤4.3% and ≤ 6.3%. The lower limits of quantification were 0.07 nmol/L for metanephrine and 0.06 nmol/L for normetanephrine. Recoveries of PFMs were in the range of 89.3–113%. The method was free from significant matrix effect, carryover and interference. Owing to its fast analysis time, more than 150 samples/day could be easily performed by a single operator. With the established reference intervals of PFMs in the Chinese population, this simple and robust LC–MS/MS method could be valuable for use in routine clinical laboratories. It is noted that the combined tests of PFMs with urinary catecholamines or urinary vanillylmandelic acid could improve specificity.